Cesarean scar endometriosis – a rare and underestimated complication - Pandey, Chandani; Shrestha, Junu; Subedi, Anjali; Rana, Apariharya (Journal of Chitwan Medical College, 2021)
Endometriosis is defined as the presence of the endometrium outside the uterine cavity. Around 8- 15 % of women of the reproductive age group have been affected by it. Abdominal scar endometriosis is a rare complication of the cesarean section and can be often misdiagnosed. We present a 39-year-old woman who has been complaining of pain and edema at the location of her cesarean incision for the past two years. The pain began on the first day of the menstrual cycle and only continued for the duration of the cycle. Swelling, which started as tiny but grew in size over time, was linked to pain. She had a similar background four years ago. Her vitals were stable during examination, as were her general and systemic examinations. There was a scar mark over the hypogastric region, as well as a 5 x 3 cm swelling in the left lateral angle of that scar. The swelling was tender. Scar endometriosis was seen on USG. Scar endometriosis was removed, and tissue was sent for histopathological examination. Now she is on injection Leuprolide 3.75mg intramuscular every monthly for a period of six months. We present this case as it is very rare complication and being underestimated by patient.